"Estilo de vida y rendimiento académico del estudiante de Enfermería de la Universidad Nacional de Trujillo. 2008" - León Castro, Verónica Elizabeth (2009)
This descriptive research and correlational cross, was conducted during the months of August through November 2008 at the School of Nursing at the National University of Trujillo, with the purpose of determining the influence of lifestyle on academic achievement Student nurses. The universe was made up of 348 students from the School of Nursing at the University of registered Trujillo current academic year 2007 - II. The sampling was random cycles in pairs (II, IV, VI, VIII and X) for a sample of 187 (p = 0.45). We used two tools: Scale the Lifestyle (Cronbach's alpha reliability = 0.98) and Format of Academic Performance. The information obtained was tabulated and processed through the statistical test of the Chi Square (X2) and Pearson correlation. The results show that the largest population in the nursing student from the National University of Trujillo introduced a high lifestyle, and a regular academic performance. We found significant relationship between lifestyle and academic achievement (p = 0.042), with higher prevalence in the dimensions of self-responsibility in health, exercise, support and interpersonal stress management.